4D Printing: An Innovative Technology For Self-transforming Structures and Multidisciplinary Applications - K. Vijaya Sri, (Asian Journal of Pharmaceutics (AJP), 2024)
4D printing, an innovative technology merging conventional additive manufacturing with smart materials and external stimuli, empowers objects to undergo transformative processes over time, exhibiting qualities like selfsensitivity, self-assembly, and self-healing. This technology harbors the potential to reshape modern construction practices, aligning with the demand for autonomous, energy-efficient, and environmentally sustainable structures. Furthermore, 4D printing proves valuable in medicine and aerospace. 4D printing can revolutionize aerospace manufacturing and design by enabling the creation of smart, adaptive, and highly efficient components and structures that can enhance the performance, reliability, and sustainability of aerospace systems. In the domain of conventional robotics, rigid materials such as metals, hard plastics, and ceramics are predominantly employed in the construction of robotics that can efficiently respond to a multitude of stimuli. Textiles offer self-sustainability, reduced material consumption, and enhanced adaptability. Despite challenges, 4D printing holds significant potential across various domains, urging substantial research and development efforts for its successful integration.